PENINGKATAN DAYA TARIK USAHA WISATA KAIN TENUN DONGGALA DI DESA TOWALE KABUPATEN DONGGALA - Vitayanti Fattah; Djayani Nurdin; Elimawati Rombe; Bakri Hasanuddin; Mohammad Nofal; Hatma Hatma; Anisah Anisah (Jurnal Abdimas Bina Bangsa, 2023)
The weavers' community in Towale Village remains primarily focused on the traditional textile weaving process, aiming to uphold their ancestral customs. They have yet to view weaving as a means to support their families financially. Consequently, the goal of this community service project is to enhance the appeal of Donggala's woven textile tourism industry through recreational, attraction, and educational activities accessible to tourists visiting Towale Village. The execution of this community service project comprises three phases: preparation, implementation, and evaluation. The outcomes of this project can enhance the weavers' knowledge, motivation, creativity, and innovation in Towale Village, ultimately boosting the attractiveness of the Donggala Woven Textile Tourism Business